The Inner Conflict of the Character Dinda in the Novel Kisah untuk Geri by Erisca Febriani - Cahyati, Sherly Dwi (Politeknik Siber Cerdika Internasional, 2025)
This article tries to analyze the inner conflict experienced by the main character, Dinda, in the novel Kisah untuk Geri by Erisca Febriani. The novel was chosen as the object of research because this novel contains the inner conflict of Dinda's character researched using the study of literary psychology. This article aims to: (1) show the character Dinda's inner conflict with other characters, (2) identify the causes of inner conflict based on the personality structure of Sigmund Freud's perspective literary psychology theory, and (3) show Dinda's character has happiness again. The method used in this research is descriptive analysis method. Data is obtained through case studies and collecting data related to Dinda's inner conflict. Based on the results of the research conducted, it shows that: (1) a situation created as a result of actions and behaviors that cause changes in the activities, attitudes, and roles of the closest people, and (2) Dinda's character resolves inner conflict.